Formation of Zintl Ions and Their Configurational Change during Sodiation in Na-Sn Battery - Choi, Yong-Seok; Byeon, Young-Woon; Ahn, Jae-Pyoung; Lee, Jae-Chul (AMER CHEMICAL SOC, 2017)
Despite their large theoretical storage capability, Na-Sn batteries exhibit poor round-trip energy efficiencies as compared to Li-Si batteries. Here, we report the results of a comprehensive study to elucidate how and why Na-Sn batteries exhibit such a low energy efficiency. As a convincing evidence for this behavior, we observed that the resistivity of the Sn anode increased by 8 orders of magnitude during in situ sodiation experiments, which is attributed to the formation of electrically resistive Zintl ions in the sodiated Sn. Continual sodiation induced the development of residual stresses at the Sn anode and caused the distortion of Zintl ions from their ideal configuration. This distortion caused a change in the electronic structure, resulting in the increased resistivity of the sodiated Sn. Our findings offer some solutions that can be used to improve the energy efficiency of Na-Sn batteries.
Keywords: SODIUM-ION; ELECTRICAL-RESISTIVITY; STORAGE; PSEUDOPOTENTIALS; NANOPARTICLES; EQUILIBRIUM; CHALLENGES; LITHIATION; INSERTION; ELECTRODE